2021
DOI: 10.1136/tsaco-2021-000677
|View full text |Cite
|
Sign up to set email alerts
|

Making your geriatric and palliative programs a strength: TQIP guideline implementation and the VRC perspective

Abstract: BackgroundOlder patients compose approximately 30% of trauma patients treated in the USA but make up nearly 50% of deaths from trauma. To help standardize and elevate care of these patients, the American College of Surgeons (ACS) Trauma Quality Improvement Program’s best practice guidelines for geriatric trauma management was published in 2013 and that for palliative care was published in 2017. Here, we discuss how palliative care and geriatrics quality metrics can be tracked and used for performance improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…The TQIP GTP guidelines for optimal care 27 are mindful of inherent health care limitations but encourage additional resources and expertise to address the needs of this population. 28 We showed that the programs offered to geriatric patients do not necessarily need so many subset pathways, which can further contribute to confusion, inefficiency, or cost. A single multidisciplinary team specializing in geriatric care and attuned to geriatric needs can be used effectively for trauma or general geriatric populations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The TQIP GTP guidelines for optimal care 27 are mindful of inherent health care limitations but encourage additional resources and expertise to address the needs of this population. 28 We showed that the programs offered to geriatric patients do not necessarily need so many subset pathways, which can further contribute to confusion, inefficiency, or cost. A single multidisciplinary team specializing in geriatric care and attuned to geriatric needs can be used effectively for trauma or general geriatric populations.…”
Section: Discussionmentioning
confidence: 88%
“…These teams can be costly if used only for trauma patients. The TQIP GTP guidelines for optimal care 27 are mindful of inherent health care limitations but encourage additional resources and expertise to address the needs of this population 28 …”
Section: Discussionmentioning
confidence: 99%
“… 39 Ho et al demonstrated that specific initiatives, including targeted education, consultations, and nurse-led frailty screening, improved local metrics and outcomes after institutional gap analyses demonstrated areas for improvement. 40 …”
Section: Balancing Financial and Staff Burdens Of Overtriagementioning
confidence: 99%
“…4 5 Shortly after the ACS-TQIP best practice guideline was released, a number of Level 1 trauma centers began implementing and validating practice management guidelines (PMGs) for the role of palliative care in trauma patients, and quickly found that these guidelines increased patient satisfaction, particularly for the care of geriatric trauma patients. 7…”
Section: Introductionmentioning
confidence: 99%